Pemberdayaan Usaha Mikro dan Kecil (UMK) oleh Dinas Perdagangan Koperasi dan UMKM Kabupaten Lima Puluh Kota dan Pengaruhnya Terhadap Kinerja UMK - Melisa Putri; Jon Kenedi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research is motivated by the author's observations which show that there are still many MSEs who face various problems in running their businesses. This research aims to find out how empowerment is carried out by the Limapuluh Kota Regency Cooperative Trade and MSME Service and to find out the impact of this empowerment on the performance of MSEs that have taken part in the empowerment provided. This research is descriptive research with a qualitative approach. Data collection techniques used were observation, interviews and documentation. Data analysis techniques use data collection, data reduction, data presentation and drawing conclusions. And there were 7 informants in this study. The results of this research show that the empowerment provided by the Limapuluh Kota Regency Cooperative Trade and MSME Service is in the form of training, including product improvement training, financial managerial training, marketing digitalization training, technical guidance on business licensing, entrepreneurship training and MSE literacy to obtain certification. halal. And the empowerment provided influences the performance of MSEs which results in an increase in sales turnover from the previous year.